Exact solutions on unsteady convective flow of viscous, casson, second grade and maxwell nanofluids - Sidra, Aman (2020)
The heat and mass transfer flow of Newtonian and non-Newtonian nanofluids caused by convection has much practical significance, such as in industries, chemicals, cosmetics, pharmaceuticals and engineering. In this thesis, the unsteady convection flows of Newtonian, non-Newtonian and non-Newtonian hybrid nanofluids such as Casson hybrid, second grade and Maxwell nanofluids in a vertical channel or past a vertical plate will be studied. Carbon nanotubes (CNTs), graphene, cobalt, copper and alumina nanoparticles are used for the enhancement of heat transfer rate of fluids in this research work. Nanofluids have a range of applications in automobiles as coolants, microelectronics, microchips in computer, fuel cells and biomedicine. The problem of free and mixed convection flow of nanofluids is studied in a porous as well as non-porous media, with or without magnetohydrodynamics (MHD) influence. Other conditions like oscillating vertical plate, radiation effect and heat generation have been considered. The idea of Caputo time fractional derivative is used in some problems which is a novel topic nowadays. The advantage of fractional derivative is that the range of derivative increases in this case and the derivative of variable are used for a range of numbers. Appropriate non-dimensional variables are used to reduce the dimensional governing equations along with imposed initial and boundary conditions into dimensionless forms. The exact solutions for velocity, temperature and concentration are acquired via Laplace Transform technique and, in some places, regular perturbation technique along with inverse Laplace transform i.e. Zakian technique. The corresponding expressions for skin friction, Nusselt number and Sherwood’s number have been calculated. The outcomes acquired are plotted via computational software MathCAD-15 using the specific thermophysical properties of nanoparticles and base fluids. The graphical outcomes have been discussed to delineate the impact of various embedded parameters such as radiation parameter, Peclet number, Grashof number, fractional parameter and volume fraction of nanoparticles. Throughout the objectives, velocity of the nanofluid is found to be increasing with increasing thermal/solutal Grashof number, radiation parameter while decreasing with volume fraction of nanoparticles. Temperature profile increases with radiation parameter, heat generation and volume fraction. Thermal conductivity and Nusselt number of the nanofluids exhibit significant increment with increasing volume fraction.